The incidence of storage rots after postharvest apple washing - Scheper, R.W.A.; Rogers, D.J.; Walker, J.T.S.; Manning, M.A.; Wood, P.N. (New Zealand Plant Protection, 2007)
The effect of four postharvest apple washing treatments and two unwashed treatments on fruit surface microflora and the development of storage rots in punctured and uninjured fruit were assessed A significantly higher incidence of storage rot was observed in punctured apples (1635) than in uninjured apples (13) after washing in water with high fungal populations (P